Aplikasi Evidence Based Nursing Hand-Held Fan Therapy pada Pasien Kanker Paru - Noviantari, Komang; Sitorus, Ratna; Aryani, Denissa Faradita; Komalawati, Dedeh; Dasat, Mariam (Journal of Telenursing (JOTING), 2023)
This study aims to prove the application of evidence-based nursing hand-held fan therapy for dyspnea in lung cancer patients. The method used was pre-experimental, with a sample size of 10 lung cancer patients. The results of the study showed that there was a significant effect of the application of hand-held fan therapy on dyspnea, respiratory rate, and SpO2 in lung cancer patients (p<0.05). In conclusion, hand-held fan therapy can reduce shortness of breath, reduce respiratory rate, and increase oxygen saturation in lung cancer patients. Keywords: Dyspnea, Hand-Held Fan Therapy, Nursing Intervention, Lung Cancer